Peranan Perception Of Digital Celebrities Terhadap Live-Stream Shopping Intentions - Kelly Kelly; Mohamad Trio Febriyantoro (LPPM Universitas BSI, 2022)
ABSTRACTSeeing the growing of live streaming and commercial value that be generated but the research on live streaming trade is still in the early stage. And there are several previous studies with different research results regarding the influence of digital celebrity perceptions on consumer shopping intentions. So this study aims to assess the antecedents of live streaming shopping intentions by integrating Perception of Digital Celebrities with Uses and gratifications theory. This study uses a quantitative approach, the data used in this study is primary data which obtained by distributing questionnaires from 116 Indonesian consumers. Data were analyzed using Structural Equation Modeling based on Partial Least Square through WarpPLS® 7.0. The results of this study indicate that the perception of digital celebrities has no significant effect on consumers' live streaming shopping intentions. The results of the study show that individuals are motivated by hedonic gratification (Perceived Enjoyment), utilitarian (Perceived Utility), and social (Social Interaction). As well as Perceived Enjoyment, Perceived Utility and Social Interaction mediate the relationship between Perception of Digital Celebrities and Live-Stream Shopping Intentions.Keywords: E-commerce, Live-stream shopping, Perception of digital celebrities, U&G